2014
DOI: 10.3831/kpi.2014.17.013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sumsu (Bufonis venenum) Pharmacopuncture Treatment on Depression in Mice

Abstract: Objectives:The main objective of this study was to evaluate the anti-depressant effects of pharmacopuncture using sumsu (Bufonis venenum).Methods:Animals were divided into three groups (control, sham, and experimental), with eight mice per group. The sham and the experimental groups were exposed to 2 hours of immobilization stress daily for 14 days. They were also injected with normal saline (sham) or subjected to pharmacopuncture with sumsu at the acupoints HT7, SP6, and GV20 (experimental). The depression or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
5
0
1
Order By: Relevance
“…Because the BVP in this test was made through hot water extraction, the components contained mainly serotonin. Serotonin (5-hydroxytryptamine) is also one of the main ingredients in BV [ 10 ]. It is involved in various psychiatric disorders such as depression, anxiety, obsessive symptoms and impulsivity, as well as in the regulation of the feeling of satiety [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the BVP in this test was made through hot water extraction, the components contained mainly serotonin. Serotonin (5-hydroxytryptamine) is also one of the main ingredients in BV [ 10 ]. It is involved in various psychiatric disorders such as depression, anxiety, obsessive symptoms and impulsivity, as well as in the regulation of the feeling of satiety [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is involved in various psychiatric disorders such as depression, anxiety, obsessive symptoms and impulsivity, as well as in the regulation of the feeling of satiety [ 11 ]. Therefore, BVP has therapeutic potential for treating patients with neuropsychiatric disorders such as anxiety or depression disorder [ 10 ]. Serotonin is one of the most effective pruritogens in the cheek model in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Biogenic amines include serotonin, histamine, dopamine, adrenaline, and noradrenaline. Toad's glandular secretions have been used for diseases such as depression, inflammation, memory, learning, and neurologic diseases such as AD and Parkinson's disease ( 17 18 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Choi et al [9] reported recently that BVP had therapeutic potential for treating neuropsychiatric disorders such as anxiety or depression disorder, but no side effects or toxicity of BVP have been reported so far. For that reason, we conducted an intramuscular single-dose toxicity test of BVP in Sprague-Dawley (SD) rats to determine the safety of its use safe and to estimating its appropriate dosage.…”
Section: Introductionmentioning
confidence: 99%